Incidence of asthma and wheeze in Indigenous children living in urban and regional areas - Marks, G; Reddel, H; Xuan, W; Ampon, R; Waters, A-M; Poulos, L; Zinoviev, A (My University, 2009)
Background: There is a large disparity in asthma and asthma-related outcomes in Aboriginal and Torres Strait Islander Australians compared with other Australians. Aim: The purpose of this study was to compare the incidence of asthma and wheeze over a two year interval among indigenous and non-indigenous children. Methods: In 2004, the Longitudinal Study of Australian Children recruited two cohorts aged 0–1 years (infant cohort, n=5,107) and 4–5 years (child cohort, n= 4,983). Asthma and wheeze were diagnosed by questionnaire and indigenous status was assessed by self-report. Prevalence rates at baseline and incidence rates over a two year follow-up period were compared between indigenous and non-indigenous children by calculating rate ratios. Results: In the infant cohort, of whom 4.9% were indigenous, the prevalence of wheeze at baseline was 1.86 times (95% CI 1.52–2.27) higher in indigenous than non-indigenous children but no significant difference was found in the incidence of wheeze over the following two years (IRR 1.21; 95% CI 0.93–1.58). In the child cohort, of whom 3.9% were indigenous, there was no difference in the prevalence of wheeze at baseline among indigenous (19.5%) and non-indigenous children (15.0%) (RR 1.30; 95% CI 0.96–1.75). In this cohort, the prevalence of asthma at baseline was 1.62 times (95% CI 1.18–2.21) higher in the indigenous children but the incidence of newly-diagnosed asthma over the next two years did not differ between the indigenous and non-indigenous children (IRR 0.7; 95% CI 0.33–1.44). Conclusions: The findings confirm a higher prevalence of reported asthma and wheeze in indigenous compared with non-indigenous children and show that the disparity diminishes with age during childhood. This suggests that the prevalence of wheezing illness in indigenous children is affected by events in early childhood. Support: ACAM is a collaborating unit of the AIHW and is funded by the Australian Government Department of Health and Ageing.
Keywords: Health -- Medical conditions; Children; Health and wellbeing; Children; Health; Medical conditions; Health and wellbeing